EFEKTIVITAS JAMUR Rhizoctonia binukleat TERHADAP PENERKEMBANGAN PATOGEN BUSUK BATANG VANILI (Fusarium oxysporum f.sp. vanillae) SECARA IN VITRO - Haryuni Haryuni (JURNAL ILMIAH AGRINECA, 2014)
Fusarium oxysporum f.sp. vanillae is a pathogenic fungus for vanilla plants. The fungi have a chitin cell wall that can be degraded by chitinase from the chitinolytic Rhizoctonia binucleate of fungi. The aim of this research was to determine how the interaction between the F. oxysporum f.sp. vanillae and Rhizoctonia binucleate were isolated from the plant rhizosphere. The chitinolytic activity was measured based on the clear zone around the colony in the chitin medium. The interaction of fungi was determined by an antagonistic test. This research showed that Rhizoctonia binucleate is chitinolytic, antagonist, and alternative of bio fungicide to F.oxysporum f.sp. vanillae